LABOUR INSPECTION VARIABLES AS CORRELATES OF DECENT WORK AGENDA IN EXTRACTIVE AND MANUFACTURING INDUSTRIES IN LAGOS AND OGUN STATES, NIGERIA (2011)
In response to daunting global challenges of quality of work life (QWL), the International Labour Organisation (ILO) initiated Decent Work Agenda (DWA), (suitable and productive working environment), to protect vulnerable employees and the working poor. Although previous studies have focused more on sweeping labour standards violations at work, they do not examine labour inspection (LI) system as a potent instrument for implementing DWA towards improving QWL. This study, therefore, investigated the extent to which LI variables (LI visits, labour law enforcement, safety monitoring, industrial relations, dispute resolution, intelligence monitoring) influenced compliance with DWA in selected extractive and manufacturing industries. The Descriptive survey research design of the ex post facto type was adopted. Proportionate stratified random sampling technique was adopted to select 1033 employees from 8 industries on the basis of minimum number of 50 employees in each organisation (456-Extractive Industry; 557-Manufacturing Industry), in Lagos and Ogun states given the high concentration of industries in the two states. Two instruments: LI Questionnaire (r = 0.75) and DWA Scale (r = 0.82) were used for data collection. These were complemented with a semi-structured Interview Guide. Thirteen In-depth Interview (IDI) sessions were held with Labour Officers, Personnel Officers and Union Leaders. Four research questions were raised and answered and two hypotheses were tested at 0.05 level of significance. Data from the questionnaires were analysed using descriptive statistics, Pearson Product Moment Correlation, t-Test and Multiple regression.IDI data were content analysed. LI variables significantly correlated (R=.61) with DWA (F (5, 1032) = 148.03; p<0.05) and accounted for 36% variance in the dependent measure. Components of LI contributed to DWA as follows: LI visit (β = 0.42), labour law enforcement (β = 0.40), safety monitoring (β = 0.26), industrial relations (β = 0.21), dispute resolution (β = 0.19) and intelligence monitoring (β = 0.15). LI correlated with the components of DWA as follows: Employment issues (r = 0.45), Promotion of rights at work (r = 0.42), Social protection issues (r = 0.33) and Social dialogue (r = 0.24). Further, the mediatory functions of governmental and institutional factors significantly correlated (R=.710) with the impacts of LI on DWA (F (2, 1031) = 254.53; p< 0.05). Relatively, their effects were in the following order: Policy support (β = 0.42), Resources (β = 0.38), Political will (β = 0.06) and Institutional capacity (β = 0.03). No significant difference was observed between extractive and manufacturing industries on decent work agenda (t = 0.23, df= 1031; p>0.05). The IDI result revealed poor labour inspection performance resulting in high decent work deficits in the examined industries. Labour inspection, supported by governmental and institutional factors remains a veritable tool for engendering DWA in extractive and manufacturing industries. Therefore, government and other stakeholders should give these factors priority attention to promote suitable working environment. Future studies could probe into why extractive industry is not more hazardous than manufacturing industry in Nigeria as revealed in this study.